Silicone elastomers from silylated polysaccharides

CN116917381BActive Publication Date: 2026-10-23DOW SILICONES CORP +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202280019152.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-03-22
Filing Date
2022-02-24
Publication Date
2026-10-23
Estimated Expiration
2042-02-24

AI Technical Summary

Benefits of technology

[0011]本发明的弹性体可用作化妆品的添加剂以实现化妆品期望的感官特性,特别是实现光滑、干燥、粉末状感觉。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004430803550000131
    Figure BDA0004430803550000131
  • Figure BDA0004430803550000161
    Figure BDA0004430803550000161
  • Figure BDA0004430803550000171
    Figure BDA0004430803550000171
Patent Text Reader

Abstract

A composition comprises a crosslinked polysiloxane elastomer having 2 or more carbon-oxygen-silicon linkages between a polysaccharide component and a polysiloxane component, wherein the polysaccharide component is not a cellulose or starch component.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to silicone elastomers, gels containing silicone elastomers, and pastes made from gels containing silicone elastomers. Background Technology

[0002] Polysiloxane elastomer materials are desirable in the cosmetics industry for thickening carrier fluids while imparting desired sensory properties to cosmetics, particularly in skin-based cosmetics regarding the feel and tactile sensation of the elastomer-carrier fluid mixture. Polysiloxane elastomers are cross-linked gel materials that impart the smooth, dry, powdery feel desired in many cosmetics while also thickening the carrier fluid. Biorenewable and / or bio-derived materials are desirable for many applications, including in the cosmetics industry. Combining biorenewable and / or bio-derived aspects with polysiloxane-based elastomer materials, while still achieving the thickening and sensory aspects associated with polysiloxane elastomers, would be one way to advance the field of polysiloxane elastomers, particularly for use in cosmetics.

[0003] Furthermore, it is desirable for polysiloxane-based elastomers to contain biorenewable and / or bio-derived components linked to the polysiloxane component via carbon-oxygen-silicon (CO-Si) bonds rather than carbon-oxygen-carbon (COC) bonds. CO-Si bonds exhibit lower hydrolytic stability than COC bonds, making molecules with CO-Si bonds more readily degradable and environmentally friendly. Additionally, alkoxylated materials with COC bonds may contain trace levels of 1,4-dioxane, an undesirable contaminant, particularly in cosmetic materials.

[0004] Cosmetics are applied to the skin, which is frequently exposed to moisture and even washing, such as handwashing. There is a desire to identify elastomeric gels containing organic solvents that can be processed into pastes with desired wash-resistant (durable) sensory properties, making them more likely to remain on surfaces such as the skin despite exposure to rinsing or washing.

[0005] It is desirable that polysiloxane-based elastomers be highly compatible with a wide variety of organic solvents to allow their use as thickeners (gelling agents) in formulations with various organic solvent carrier fluids. The elastomer is compatible with the organic solvent if it can form a gel with a solvent that is more viscous than the solvent alone. Furthermore, it is desirable that the gel of the elastomer and solvent can form a solvent-compatible paste by creating a homogeneous mixture, preferably translucent or even transparent to visible light, and stable against phase separation.

[0006] Furthermore, it is desirable to identify a method for preparing polysiloxane elastomers using a hydrosilylation reaction without causing yellowing or discoloration of the reaction products. Hydrosilylation reactions typically use platinum-based catalysts. Platinum-based catalysts generally result in a yellow color in the reaction products. It is desirable to avoid this yellowing color, particularly in cosmetic applications. Summary of the Invention

[0007] This invention provides a polysiloxane-based elastomer that thickens a carrier fluid while imparting a desired smooth, dry, powdery feel to the mixture of the carrier fluid and the elastomer. The polysiloxane-based elastomer comprises a polysaccharide component, which is a bio-renewable and / or bio-derived component. Furthermore, the polysiloxane-based elastomer of this invention connects the polysaccharide component to the polysiloxane component via CO-Si linkages. Specifically, the polysaccharide component is connected to the polysiloxane component via at least two CO-Si linkages, wherein the polysiloxane component serves as a crosslinking component in the polysiloxane-based elastomer. Further, this invention provides a polysiloxane-based elastomer that gels with various organic solvents and can be formulated into a paste exhibiting higher wash resistance (durability) than other polysiloxane elastomers. The polysiloxane-based elastomers of this invention tend to be highly compatible with a wide range of organic solvents because the polysiloxane-based elastomers form mixtures with organic solvent carrier fluids that are more viscous than the carrier fluid, and can form uniform, translucent or transparent pastes that are stable against phase separation. The polysiloxane-based elastomers are prepared via a hydrosilylation reaction, which surprisingly exhibits minimal yellowing (less than 300, even less than 100, on the APHA colorimetric scale).

[0008] Part of this invention relates to the discovery of how to prepare polysaccharide intermediates having alkenyl functional groups attached to polysaccharides via CO-Si linkages. It was found that these alkenyl functional polysaccharides react with SiH-functionalized polysiloxanes to provide polysiloxane elastomer gels possessing the aforementioned desired properties.

[0009] In a first aspect, the present invention is a composition comprising a crosslinked polysiloxane elastomer having two or more carbon-oxygen-silicon links between a polysaccharide component and a polysiloxane component, wherein the polysaccharide component is not a cellulose or starch component.

[0010] In a second aspect, the present invention is a method for preparing the composition of the first aspect, the method comprising forming the crosslinked polysiloxane elastomer by a hydrosilylation addition reaction between reactants comprising: (a) a SiH-functionalized polyorganosiloxane; and (b) an alkenyl-functionalized polysaccharide characterized in that: (i) it comprises linked fructose, galactose, dehydrated galactose, or glucose units, provided that the glycosidic linkage of the glucose is α-linked; and (ii) on average, these alkenyl-functionalized polysaccharides have a molar percentage of 1 to 10 0 mol% of hydroxyl groups have been silylated with a silyl group having the structure -SiR3 linked to the polysaccharide via a CO-Si bond, wherein each R is independently selected from a hydrocarbon group having 1 to 12 carbon atoms, provided that, on average, at least 2.0 R groups per polysaccharide are terminal alkenyl groups; and (iii) the alkenyl functional polysaccharide is not silylated starch; and optionally (c) additional crosslinking additives; the reaction is carried out in the presence of (d) a platinum-based hydrosilylation catalyst; and (e) a solvent.

[0011] The elastomer of the present invention can be used as an additive in cosmetics to achieve desired sensory properties, particularly a smooth, dry, powdery feel. Detailed Implementation

[0012] When a date is not indicated by a test method number, the test method refers to the most recent test method as of the priority date of this document. References to test methods include references to both the testing association and the test method number. The following test method abbreviations and designations apply to this document: ASTM refers to ASTM International Society Methods; END refers to European Standards; DIN refers to the German Institute for Standardization; ISO refers to the International Organization for Standardization; and UL refers to Underwriters Laboratories.

[0013] Products identified by their trade names refer to compositions available under those trade names as of the priority date of this document.

[0014] "Multiple" means two or more. "And / or" means "and, or as an alternative." Unless otherwise specified, all ranges include the endpoints.

[0015] "Hydrocarbon group" refers to a monovalent group formed by removing hydrogen atoms from hydrocarbons, including alkyl groups and aryl groups.

[0016] "Alkyl" refers to a hydrocarbon group that can be derived from an alkane by removing a hydrogen atom. Alkyl groups can be straight-chain or branched.

[0017] "Aryl" refers to a group that can be formed by removing a hydrogen atom from an aromatic hydrocarbon.

[0018] A polysaccharide is a molecule consisting of two or more sugar units that are covalently linked together. Polysaccharides include substances sometimes referred to as disaccharides and oligosaccharides. A disaccharide is a molecule consisting of two sugar units that are covalently linked together. An oligosaccharide is a molecule consisting of 3 to 10 sugar units covalently linked in a chain, which may be a cyclic chain.

[0019] Regarding polysaccharides, "side groups" refer to groups other than hydrogen atoms that extend from the polysaccharide backbone, particularly those extending from carbon atoms on the pyranose or furanose rings of the polysaccharide backbone. Adjacent sugar groups in a polysaccharide are not considered "side groups" but rather part of the polysaccharide backbone.

[0020] "Starch" refers to a combination of amylose and amylopectin.

[0021] "APHA" refers to the American Public Health Association.

[0022] "Terminal alkenyl" refers to a monovalent aliphatic hydrocarbon group that can be derived from an alkene having a carbon-carbon double bond (C=C), wherein the carbon atom of C=C is the terminal carbon, and wherein the monovalent aliphatic hydrocarbon group can be derived by removing a hydrogen atom from a carbon atom other than the terminal carbon atom in C=C.

[0023] This invention relates to compositions comprising crosslinked polysiloxane elastomers, wherein the crosslinked polysiloxane elastomers contain two or more carbon-oxygen-silicon (CO-Si) bonds between a polysaccharide component and a polysiloxane component. The elastomer is a crosslinked polymer with elastic properties, meaning it is not so heavily crosslinked that it is a rigid material, but rather sufficiently crosslinked that it is insoluble in solvents. In fact, the elastomer actually swells in the solvent to form a gel rather than dissolving in the solvent. One characteristic of the elastomer of this invention is that it can thicken solvents even to the point of forming a non-flowing gel at 25 degrees Celsius (°C), while also being able to be processed (e.g., gelled in a solvent and then subjected to shear mixing) to form pastes with desired sensory properties, such as a smooth, dry, powdery feel of the resulting thickened material, comparable to current polysiloxane additives used to achieve such desired sensory properties.

[0024] Crosslinked polysiloxane elastomers comprise polysaccharide-based crosslinking agents interconnected with polysiloxane segments via CO-Si linkages. The CO-Si linked carbon atoms are preferably hexose carbons of the polysaccharide. Typically, the CO-Si linked silicon atoms are further linked to silicon atoms of the polysiloxane via divalent hydrocarbon groups, which are present in two or more, and may have three or more, four or more, five or more, or even six or more, while typically having 12 or fewer, typically 10 or fewer, eight or fewer, six or fewer, four or fewer, or even three or fewer carbon atoms. For example, the divalent hydrocarbon group may have the general chemical formula -(CH2). n - a straight chain, where n is the number of carbon atoms in the divalent hydrocarbon group. Common divalent hydrocarbon groups used in the crosslinked polysiloxanes of this invention have two carbon atoms. The CO-Si linkage and the divalent hydrocarbon linkage between the Si of the CO-Si and the polysiloxane component are characteristic features of the unique manner of preparing the crosslinked polysiloxane elastomers of this invention. In particular, the crosslinked polysiloxane elastomers are prepared by a hydrosilylation reaction between a SiH-functionalized polysiloxane and a polysaccharide intermediate having two or more CO-SiR3 groups, wherein each R is independently selected from hydrocarbon groups having 1 to 12 carbon atoms, provided that each polysaccharide has at least one R with a terminal unsaturated carbon-carbon double bond on average. Preferably and generally, the carbon of the CO-SiR3 group is the carbon of the hexose of the polysaccharide. The hydrosilylation reaction involves the reaction between the terminal unsaturated carbon-carbon double bond (C=C) of the CO-SiR3 group and the SiH group of the polysiloxane, producing a residual R group containing C=C that acts as a divalent carbon linking the CO-Si linkage and the polysiloxane. It is worth noting that the connection between the sugar and the siloxane may not contain any functional group selected from ethers, esters, polyurethanes and ureas, or any combination of more than one functional group.

[0025] The polysaccharide in the crosslinked polysiloxane elastomer is neither a cellulose nor a starch component. It has been found that when the sugar component is cellulose or starch, the polysaccharide intermediates used to prepare the elastomers of this invention are insoluble in nonpolar aromatic solvents. This insolubility in nonpolar aromatic solvents makes the polysaccharide intermediates less versatile and limits the solvents that can be used to prepare the crosslinked polysiloxane elastomers.

[0026] Desiredly, the polysaccharide component of the crosslinked polysiloxane elastomer comprises sugar units linked to fructose, galactose, dehydrated galactose, or glucose, provided that the glycosidic linkage of glucose is α-linked. Desiredly, the polysaccharide component of the crosslinked polysiloxane elastomer has only side groups selected from the group consisting of -OSiR3 groups, -CH2OSiR3 groups, -OH, and -CH2OH, in addition to the linkage with the polysiloxane. Typically, the polysaccharide component contains an average of 2 to 2000 linked sugar units. Polysaccharides may include 2 or more, 3 or more, 4 or more, 5 or more, 6 or more, 7 or more, 8 or more, 9 or more, 10 or more, 20 or more, 40 or more, 60 or more, 80 or more, even 100 or more, or 200 or more, and typically include 2000 or less, 1800 or less, 1600 or less, 1400 or less, 1200 or less, 1000 or less, 800 or less, 600 or less, 400 or less, 200 or less, 100 or less, 80 or less, 60 or less, 40 or less, 20 or less, or even 10 or less sugar units per molecule. The average number of sugar units per molecule in the polysaccharide component is determined from the polysaccharide starting material used to prepare crosslinked polysiloxane elastomers. The number of sugar units in the polysaccharide used to prepare crosslinked polysiloxane elastomers may be determined by the supplier based on common sense in the art regarding how many sugar units a particular polysaccharide contains, or, if neither of these is possible, by gel permeation chromatography using standard techniques.

[0027] The polysiloxane component of the crosslinked polysiloxane elastomer is crosslinked via polysaccharide groups. The degree of crosslinking should be sufficient to achieve gelation in the presence of a solvent. The polysiloxane component can be linear, branched, or cyclic. Typically, the polysiloxane component contains one or any combination of polysiloxane units selected from the following: R3SiO 1 / 2 ("M-type unit") R2SiO 2 / 2 ("D-type unit") RSiO 3 / 2 ("T-type unit) and SiO 4 / 2(“Q” type units), wherein each R is independently selected from hydrogen, hydrocarbon groups, and substituted hydrocarbon groups, and the oxygen atom listed in the unit refers to oxygen bonded to silicon atoms of two different siloxane units, wherein the subscript on oxygen indicates the amount of oxygen shared in the molecule, and the sharing of oxygen atoms with another siloxane unit is specified by dividing the molecule by 2. Desiredly, the polysiloxane component is linear, comprising M-type and D-type polysiloxane units, and has a degree of polymerization of zero or more, 1 or more, 2 or more, 3 or more, 4 or more, 5 or more, 6 or more, 7 or more, 8 or more, 9 or more, 10 or more, 15 or more, 20 or more, 30 or more, 40 or more, 50 or more, 75 or more, 100 or more, even 150 or more, and most preferably 200 or less, and may be 150 or less, 100 or less, 75 or less, 50 or less, 40 or less, 30 or less, 20 or less, even 10 or less. If the DP of the linear polysiloxane exceeds 200, the resulting elastomer tends to be weak and flexible as a gel. Most desirablely, the DP is 20 or less, preferably 15 or less or even lower, to maximize the concentration of the biorenewable polysaccharide component in the crosslinked polysiloxane elastomer.

[0028] Based on the total weight of polysaccharides, polysiloxanes, and other crosslinking components, crosslinked polysiloxane elastomers typically contain 1 wt% or more, 5 wt% or more, and may contain 10 wt% or more, 15 wt% or more, 20 wt% or more, 25 wt% or more, 30 wt% or more, 35 wt% or more, 40 wt% or more, 45 wt% or more, 50 wt% or more, 55 wt% or more, 60 wt% or more, 65 wt% or more, 70 wt% or more, 75 wt% or more, 80 wt% or more, 85 wt% or more, or more than ...70 wt% or more, 75 wt% or more, 80 wt% or more, 85 wt% or more, or more than 10 wt% or more, 15 wt% or more, 20 wt% or more, 20 wt% or more, 60 wt% or more, 65 wt% or more, 70 wt% or more, 75 More, even 89 or 90 wt% or more, and usually contains 90 wt% or less, 89 wt% or less, 85 wt% or less, 80 wt% or less, 75 wt% or less, 70 wt% or less, 65 wt% or less, 60 wt% or less, 55 wt% or less, 50 wt% or less, 45 wt% or less, 40 wt% or less, 35 wt% or less, 30 wt% or less, 25 wt% or less, 20 wt% or less, 15 wt% or less, 10 wt% or less, or even 5 wt% or less of polysaccharide components.

[0029] Crosslinked polysiloxane elastomers may contain crosslinking components different from the polysaccharide component. The additional crosslinking component establishes crosslinks between sugar-free units between the polysiloxane chains. Examples of suitable crosslinking components include vinylsiloxanes, hexenylsiloxanes, allyl polyethers, methalyl polyethers, and residues of di-terminated olefins (i.e., olefins having carbon-carbon double bonds at both ends) (i.e., the component remaining after the alkenyl groups of the crosslinking agent react with the SiH groups on the polysiloxane to form bonds). The additional crosslinking component may constitute 0 mol% or more of the crosslinking bonds in the crosslinked polysiloxane elastomer, optionally 5 mol% or more, 10 mol% or more, 15 mol% or more, 20 mol% or more, 25 mol% or more, 30 mol% or more, 35 mol% or more, 40 mol% or more, 45 mol% or more, 50 mol% or more, 55 mol% or more, 60 mol% or more, 65 mol% or more, 70 mol% or more, 75 mol% or more, 80 mol% or more, or even 85 mol% or more. The percentages are typically 90 mol% or less, 85 mol% or less, 80 mol% or less, 75 mol% or less, 70 mol% or less, 65 mol% or less, 60 mol% or less, 55 mol% or less, 50 mol% or less, 45 mol% or less, 40 mol% or less, 35 mol% or less, 30 mol% or less, 25 mol% or less, 20 mol% or less, 15 mol% or less, 10 mol% or less, 5 mol% or less, 3 mol% or less, or even 1 mol% or less.

[0030] The compositions of the present invention may and typically also include a solvent, sometimes referred to as a carrier fluid, which swells and crosslinks the polysiloxane elastomer to form a gel. A “gel” is a diluted crosslinked system that is homogeneous and does not exhibit flow when in a steady state. “Homogeneous” means that the composition does not separate from each other. “Does not exhibit flow” means, as described in the Examples section below, that the composition does not flow when inverted in a vial. The crosslinked polysiloxane elastomer acts as a thickener for the solvent by increasing its viscosity. The solvent may be, for example, any fluid or any combination of fluids selected from the group consisting of hydrocarbons, ethers, esters, alcohols, and siloxane fluids. Examples of suitable hydrocarbon fluids include farnesane, squalane, isohexadecane, undecane, tridecane, and isododecane. Examples of suitable ether fluids include those named CETIOL. TMOE (CETIOL is a trademark of Cognis IP Management GmbH) sells less of the following materials from BASF: ethyl 3-(2,4-dimethyl-1,3-dioxolane-2-yl)propionate, ethyl glyceryl acetal levulinate, ethyl phenylethyl acetal, and isopropylidene cocoate. Examples of suitable ester fluids include isodecanyl neopentanoate, isostearyl neopentanoate, isononyl isononanoate, ethyl acetate, triglyceride caprylate, glyceryl caprylate, triheptanoate, triisostearin, diisopropyl acetate, diisopropyl adipate, diisobutyl adipate, diethylhexyl adipate, n-propyl acetate, isobutyl acetate, n-butyl acetate, trimethylolpropane trioctanoate, trimethylolpropane tridecanoate, dipolypentaerythritol hexa-C5-9 ester, C12-15 alkyl benzoate, triisooctanoate, etc. Glyceryl esters, neopentyl glycol diheptanoate, diheptyl succinate, heptyl undecenoate, propylene glycol dibenzoate, dipropylene glycol dibenzoate, ethylhexyl palmitate, ethylhexyl stearate, isopropyl laurate, hexyl laurate, isopropyl myristate, isopropyl palmitate, n-butyl stearate, propylene glycol dicaprylate, propylene glycol didecanoate, cocoyl caprylate, cocoyl decanoate, ethylhexyl cocoate, oleyl erucate, propyl heptyl octanoate, decyl oleate, hexyl decyl stearate, and propylene glycol laurate. Examples of suitable siloxane fluids include cyclic siloxanes, such as cyclotetrasiloxanes, such as DOWSIL. TM 244 fluid (DOWSIL is a trademark of The Dow Chemical Company) is available; cyclopentasiloxanes, such as DOWSIL TM 245 fluids are available; or cyclohexylsiloxanes, such as DOWSIL TM 246 Fluid-available; straight-chain and branched alkyl and aryl siloxanes, such as octyl polymethylsiloxane, such as DOWSIL TM FZ-3196 is available; and linear dimethylsiloxanes, such as DOWSIL. TM 200 fluids are available; and phenyl polytrimethylsiloxane, such as DOWSIL TM 556 fluids are available.

[0031] The solvent can be selected from the following "highly volatile" solvents: isododecane (boiling point 210°C at 101 MPa), farnesane (boiling point 252°C at 101 MPa), undecane (boiling point 195°C at 101 MPa), n-dodecane (boiling point 216°C at 101 MPa), and tridecane (boiling point 234°C at 101 MPa). These solvents form gels that can be converted into pastes with higher wash durability than pastes made from conventional pure silicone elastomers.

[0032] Based on the total weight of the solvent and the crosslinked polysiloxane elastomer, the solvent concentration in the gelled crosslinked polysiloxane elastomer composition is preferably 25 wt% or more, preferably 30 wt% or more, 35 wt% or more, 40 wt% or more, 45 wt% or more, 50 wt% or more, 55 wt% or more, 60 wt% or more, 65 wt% or more, 70 wt% or more, 75 wt% or more, or even 80 wt% or more, while typically 85 wt% or less, 80 wt% or less, 75 wt% or less, 70 wt% or less, 65 wt% or less, 60 wt% or less, 55 wt% or less, 50 wt% or less, 45 wt% or less, 40 wt% or less, 35 wt% or less.

[0033] The gel of solvent and cross-linked polysiloxane elastomer is expected to be translucent or transparent to visible light, but it can be opaque.

[0034] The gel of solvent and crosslinked polysiloxane elastomer may further include additional components, particularly those suitable for cosmetic applications. For example, the gel may contain any one or a combination of more than one of the following components: emollients, waxes, moisturizers, vegetable oils, synthetic oils, petrolatum, plant extracts, vitamins, proteins, amino acids and their derivatives, fillers, UV absorbers, sunscreens, anti-dandruff agents, antiperspirants, deodorants, skin protectants, hair dyes, fragrances, essential oils, pigments and colorants, and / or other active substances or additives suitable for cosmetic use. The additional components may be added before, during, or after the hydrosilylation reaction that produces the gel.

[0035] The gels of solvents and crosslinked polysiloxane elastomers exhibit desired properties for cosmetic applications. In particular, the gels exhibit desired sensory properties, durability, and solvent compatibility. Methods for determining and evaluating these properties are described in the following Examples section. Therefore, the crosslinked polysiloxane elastomers of the present invention, and especially the gels of solvents and crosslinked polysiloxane elastomers, are useful and desirable in cosmetic applications, such as creams, aqueous solutions, emulsions (water-in-oil or oil-in-water), oils, ointments, pastes, gels, lotions, emulsions, foams, sticks, and suspensions. Cosmetics can be used in personal care applications such as makeup, facial and body care cosmetics, leave-in hair care, and topical care products.

[0036] The crosslinked polysiloxane elastomers of the present invention are intended to be prepared by a hydrogenation silylation reaction between reactants comprising SiH-functionalized polysiloxanes and alkenyl-functionalized (preferably vinyl-functionalized) polysaccharides and optionally additional crosslinking additives. The SiH-functionalized polysiloxanes can be linear or branched. Each molecule of the SiH-functionalized polysiloxane contains two or more SiH functional groups. Based on the weight of the polysiloxane, the SiH content of the polysiloxane is preferably 0.02 wt% or more, 0.05 wt% or more, 0.08 wt% or more, 0.10 wt% or more, 0.15 wt% or more, 0.20 wt% or more, 0.25 wt% or more, 0.30 wt% or more, 0.35 wt% or more, 0.40 wt% or more, 0.45 wt% or more, 0.50 wt% or more, 0.55 wt% or more, 0.60 wt% or more, 0. 0.65 wt% or more, 0.70 wt% or more, 0.75 wt% or more, 0.85 wt% or more, 0.90 wt% or more, even 0.95 wt% or more, typically 1.5 wt% or less, 1.25 wt% or less, 1.0 wt% or less, and may be 0.9 wt% or less, 0.8 wt% or less, 0.6 wt% or less, 0.5 wt% or less, 0.4 wt% or less, even 0.3 wt% or less, or 0.2 wt% or less. Wt%SiH refers to the mass of silicon-bonded hydrogen divided by the mass of the polymer multiplied by 100%. The SiH content is determined by infrared spectroscopy according to the method in CN103674889A.

[0037] SiH-functionalized polysiloxanes can contain any combination of M-type, D-type, T-type, and Q-type siloxane units. Desiredly, SiH-functionalized polysiloxanes are linear, containing both M-type and D-type polysiloxane units, and have a degree of polymerization of zero or more, 1 or more, 2 or more, 3 or more, 4 or more, 5 or more, 6 or more, 7 or more, 8 or more, 9 or more, 10 or more, 15 or more, 20 or more, 30 or more, 40 or more, 50 or more, 75 or more, 100 or more, even 150 or more, and most preferably 200 or less, but can be 150 or less, 100 or less, 75 or less, 50 or less, 40 or less, 30 or less, 20 or less, even 10 or less. If the DP of the linear polysiloxane exceeds 200, the resulting crosslinked polysiloxane elastomer tends to be weak and flexible as a gel. Ideally, the DP is 20 or less, preferably 15 or less or even lower, to maximize the concentration of the biorenewable polysaccharide component in the crosslinked polysiloxane elastomer.

[0038] The polysaccharide component is preferably a silylated polysaccharide comprising fructose, galactose, dehydrated galactose, or glucose units, provided that the glycosidic linkage of the glucose is α-linked, and that the silylated polysaccharide is not silylated starch; and is further characterized by having an average 1 mol% or more, preferably 5 mol% or more, 10 mol% or more, 15 mol% or more, 20 mol% or more, 30 mol% or more, 33 mol% or more, preferably 35 mol% or more, 37 mol% or more, or more. The polysaccharides contain hydroxyl groups on polysaccharides of 40 mol% or more, 50 mol% or more, 60 mol% or more, 70 mol% or more, 80 mol% or more, or even 90 mol% or more, while simultaneously containing 100 mol% or less. These hydroxyl groups are silylated with a silyl group having the structure -SiR3 and linked to the polysaccharide via a CO-Si bond, wherein each R is independently selected from a hydrocarbon group having 1 to 12 carbon atoms, provided that, on average, each polysaccharide has at least 2.0 R groups with terminal unsaturated carbon-carbon double bonds (e.g., vinyl groups). Typically, the R component of the -SiR3 group is selected from methyl groups and vinyl groups. Desiredly, the silylated polysaccharides are selected from the group consisting of: silylated α-cyclodextrin, silylated β-cyclodextrin, silylated γ-cyclodextrin, silylated maltodextrin, silylated pullulan, silylated dextran, silylated trehalose, silylated inulin, and silylated agarose. Silylated polysaccharides are expected to contain 2 to 2000 sugar units per molecule, with optional limitations on the number of sugar units bonded together, as taught above for the polysaccharide components of elastomers.

[0039] The amounts of SiH-functionalized polysiloxane and alkenyl-functionalized polysaccharide are such that the molar ratio of SiH groups to alkenyl groups in the polysaccharide is greater than 0.7, preferably 0.8 or more, 0.9 or more, 1.0 or more, 1.1 or more, 1.2 or more, 1.3 or more, or even 1.4 or more, while typically 1.5 or less, preferably 1.4 or less, 1.2 or less, 1.1 or less, or even 1.0 or less. The SiH to alkenyl ratio is determined by the molar ratio of the components used in the reaction and the average molar amount of each functional group on the components used. The molar concentration of SiH can be determined by the supplier of the SiH-functionalized polysiloxane, or if not available from the supplier, by infrared spectroscopy according to the method of CN103674889A. The molar concentration of alkenyl groups can be determined by the components used to prepare the alkenyl-functionalized polysaccharide and / or the alkenyl-functionalized polysaccharide. 1 To determine this, use 1H NMR analysis.

[0040] Hydrosilylation reactions also require platinum-based hydrosilylation catalysts. Platinum-based hydrosilylation catalysts include compounds and complexes such as platinum(O)-1,3-divinyl-1,1,3,3-tetramethyldisiloxane (Karstedt's catalyst), H2PtCl6, di-μ.-carbonyldi-π.-cyclopentadienyldinickel, platinum-carbonyl complexes, platinum-divinyltetramethyldisiloxane complexes, platinum cyclovinylmethylsiloxane complexes, platinum acetylacetonate (acac), platinum black, platinum compounds (such as chloroplatinic acid, chloroplatinic acid hexahydrate, the reaction product of chloroplatinic acid with a monohydric alcohol, bis(ethyl acetoacetate)platinum, bis(acetylacetonate)platinum, platinum dichloride), and platinum compounds complexed with olefins or low molecular weight organopolysiloxanes, or platinum compounds microencapsulated in matrix or core-shell structures. The hydrosilylation catalyst may be part of a solution comprising a platinum complex with a low molecular weight organopolysiloxane, including a platinum complex of 1,3-divinyl-1,1,3,3-tetramethyldisiloxane. These complexes may be microencapsulated in a resin substrate. The catalyst may be a platinum complex of 1,3-divinyl-1,1,3,3-tetramethyldisiloxane. Based on the weight of the polysaccharide component, polysiloxane component, solvent, and any additional crosslinking agent, the concentration of the platinum-based hydrosilylation catalyst in hydrosilylation is typically 5 parts per million by weight (ppm) or more, preferably 10 ppm or more, and may be 25 ppm or more, 50 ppm or more, or even 75 ppm or more. It is typically 500 ppm or less, 400 ppm or less, 300 ppm or less, 200 ppm or less, and preferably 100 ppm or less, and may be 90 ppm or less, 80 ppm or less, 70 ppm or less, 60 ppm or less, or even 50 ppm or less.

[0041] The hydrosilylation reaction that forms the elastomer may also include additional crosslinking additives. Each molecule of the additional crosslinking additive contains multiple alkenyl functional groups and acts as a crosslinking component in addition to the alkenyl functional polysaccharide. Additional crosslinking additives are not required, but may be present to supplement crosslinking. Examples of suitable additional crosslinking additives include vinyl-terminated polydimethylsiloxanes, poly(dimethyl, methyl vinyl)siloxanes, vinyl-terminated poly(dimethyl, methyl vinyl)siloxanes, hexenyl-terminated polydimethylsiloxanes, 1,5-hexadiene, 1,11-dodecadiene, 1,15-hexadecadiene, bis(methallyl)poly(ethylene oxide), bis(allyl)poly(ethylene oxide), bis(methallyl)poly(propylene oxide), and bis(allyl)poly(propylene oxide).

[0042] If present, the additional crosslinking additive provides zero mol% or more, optionally 5 mol% or more, 10 mol% or more, 15 mol% or more, 20 mol% or more, 25 mol% or more, 30 mol% or more, 35 mol% or more, 40 mol% or more, 45 mol% or more, 50 mol% or more, 55 mol% or more, 60 mol% or more, 65 mol% or more, 70 mol% or more, 75 mol% or more, 80 mol% or more, or even 85 mol% or more, relative to the combined molarity of the alkenyl functional polysaccharide and the additional crosslinking additive. The concentration of alkenyl groups is present in mol% or more and is typically 90 mol% or less, 85 mol% or less, 80 mol% or less, 75 mol% or less, 70 mol% or less, 65 mol% or less, 60 mol% or less, 55 mol% or less, 50 mol% or less, 45 mol% or less, 40 mol% or less, 35 mol% or less, 30 mol% or less, 25 mol% or less, 20 mol% or less, 15 mol% or less, 10 mol% or less, 5 mol% or less, 3 mol% or less, or even 1 mol% or less.

[0043] The reaction is typically carried out in a solvent compatible with both the polysiloxane and the resulting silylated polysaccharide, and becomes a carrier fluid that swells the elastomer into a gel when the elastomer is prepared. This solvent can be, for example, selected from the group consisting of hydrocarbons, ethers, esters, alcohols, and siloxane fluids, as previously taught above for solvents included in gelled crosslinked polysiloxane elastomers. Based on the combined weight of the solvent, SiH-functionalized polysiloxane, alkenyl-functionalized polysaccharide, and any other crosslinking additives, the concentration of the solvent in the reaction mixture is typically 25 wt% or more, preferably 30 wt% or more, 35 wt% or more, 40 wt% or more, 45 wt% or more, 50 wt% or more, 55 wt% or more, 60 wt% or more, 65 wt% or more, 70 wt% or more, 75 wt% or more, or even 80 wt% or more, while typically 85 wt% or less, 80 wt% or less, 75 wt% or less, 70 wt% or less, 65 wt% or less, 60 wt% or less, 55 wt% or less, 50 wt% or less, 45 wt% or less, 40 wt% or less, 35 wt% or less.

[0044] Hydrosilylation is carried out by combining a solvent, a SiH-functionalized polysiloxane, an alkenyl-functionalized polysaccharide, any other crosslinking agent, and a platinum-based catalyst and stirring them to form a reaction mixture (typically at 25°C). The reaction mixture is typically heated to a temperature in the range of 70-90°C while stirring. Stirring continues until a gel forms and then stops. The gel is heated for a period of time to complete the reaction, typically by placing the gel in an oven at 70°C for 3 hours. Specific examples of the hydrosilylation reaction for preparing the crosslinked polysiloxane elastomer of the present invention are provided in the Examples section below. The hydrosilylation reaction produces a crosslinked polysiloxane elastomer gel comprising the crosslinked polysiloxane elastomer of the present invention, which has been swollen to form a gel using the solvent used in the hydrosilylation reaction. The hydrosilylation reaction prepares the crosslinked polysiloxane elastomer of the present invention and the crosslinked polysiloxane elastomer gel of the present invention. The crosslinked polysiloxane elastomer gel may be transparent, translucent, or opaque relative to visible light, but is preferably transparent.

[0045] Hydrosilylation reactions can be carried out in the absence of unsaturated organic molecules other than silylated polysaccharides and / or unsaturated siloxanes.

[0046] Crosslinked polysiloxane gels can be shear-mixed to form a paste with or without additional solvents and / or post-curing quenchers. Suitable post-curing quenchers include any one or more combinations selected from the group consisting of: vinyl tert-butyldimethylsilane, vinyl diethylmethylsilane, vinyl ethyldimethylsilane, vinyl triethylsilane, vinyl trimethylsilane, divinyl dimethylsilane, divinyl tetramethylsilane, vinyl pentamethyldisiloxane, 1,3-divinyl tetramethyldisiloxane, tetra(dimethylvinylsilyl)silicate, vinylsilane, terminal straight-chain vinylsiloxane, side-chain straight-chain vinylsiloxane, terminal branched vinylsiloxane, side-chain branched vinylsiloxane, side-chain and terminal branched siloxanes, and cyclic vinylsiloxanes. The resulting paste can be translucent or transparent to visible light, homogeneous, stable against phase separation, and possess the desired sensory properties described in the Examples section below.

[0047] Example

[0048] Table 1 lists the components used to prepare alkenyl functionalized polysaccharides, which are used to prepare crosslinked polysiloxane elastomers described in the next section.

[0049] Table 1

[0050]

[0051] MALTRIN is a trademark of a grain processing company.

[0052] Preparation of alkenyl functional polysaccharides

[0053] Samples were prepared using the formulations in Table 2 as follows. For those samples indicating that the polysaccharide was dried, the polysaccharide was dried in a vacuum (1.3 kPa, 10 mm Hg) at 90 °C for 24 hours prior to the reaction. The specified amounts of polysaccharide, silazane, catalyst, and solvent were added to 40 mL vials. A PTFE stir bar was added, and the vials were inertized by purging with nitrogen and sealing with a diaphragm. The vials were placed on a heating block and heated to the specified temperature for the specified duration while stirring. The samples were then cooled and dried in a vacuum (1.3 kPa, 10 mm Hg) for 24 hours to obtain the silylated polysaccharide samples.

[0054] Through proton nuclear magnetic resonance spectroscopy ( 1 The degree of hydroxyl silylation and alkenyl substitution was determined by ¹H NMR. For example, 10 mg of sample was dissolved in 0.6 mL of d6-benzene and... 1¹H NMR analysis was performed on a 400 MHz Varian NMR spectrometer. A 5-second acquisition time and a 15-second relaxation delay were used, and 16 scans were collected. The final spectrum of residual benzene was referenced at δ 7.16 ppm. Regions for specific groups in the spectrum were integrated as follows: the unsaturated region (“U”) at δ 5.6–6.5 ppm to account for all three protons of the vinyl group (“U” = “A”) or one proton of other terminal alkenyl groups (3“U” = “A”), the sugar region (“S”) at δ 3.6–4.6 ppm, and the methyl region (“M”) at δ 0.20–0.55 ppm. The sugar region was normalized to methanediyl and methanetriylhydrogens, excluding anomeric hydrocarbons.

[0055] The following sample properties were determined based on their relevant calculations:

[0056] Mole percentage (%) - OH substitution = [(A / 3) + (M - 2 * A)] / [-OH / starting sugar] * 100

[0057] = mol% of the hydroxyl groups on the polysaccharide that have been silylated with -SiR3 via CO-Si bonds.

[0058] Molar percentage of terminal alkenyl substitution (alkenyl %) = [(A / 3)] / [(A / 3)+(M-2*A)]*100%

[0059] The terminal alkenyl group of each polysaccharide = [(alkenyl %)] * [mol% -OH substitution] * [-OH / starting sugar] * [degree of polymerization] / 10 4

[0060] in:

[0061] "[Mol%-OH / starting sugar]" is 2 for agarose, 4 for disaccharides, and 3 for all other polysaccharides within the scope of this invention.

[0062] "Degree of polymerization" refers to the number of polysaccharide units in each polysaccharide molecule, and can be obtained from the polysaccharide supplier or determined using conventional GPC methods.

[0063] For the sample insoluble in d6-benzene, the molar percentage of hydroxyl substitution was determined by neutron activation analysis (NAA). A duplicate of the analyte material was prepared by transferring 1.0 g of sample to a pre-cleaned 2-dosland polyethylene vial. Silicon standard aliquots were prepared from NIST traceable standard solutions by placing an appropriate amount into a vial similar to the sample. The aliquots were diluted with pure water to the same volume as the analyte material. A blank containing only pure water was also prepared. The analyte material, standard, and blank were analyzed according to the standard NAA procedure—irradiation at 100 kW for 2 minutes. After a 9-minute waiting period, gamma-ray spectroscopy was performed using a high-purity germanium detector. The silicon concentration (wt% Si) was determined using standard comparative techniques with CANBERRA software. The mol% -OH substitution was calculated using the following calculations:

[0064] Mol% -OH substitution = ([MW of the starting polysaccharide repeating unit] * [wt% Si]) / {(28 - 84 * [wt% Si] / 100) * [-OH / starting sugar]}.

[0065] This value corresponds to the mol% of hydroxyl groups on the polysaccharide that have been silylated with -SiR3 via CO-Si bonds.

[0066] in:

[0067] [MW of repeating polysaccharide repeating units] is 154 for agarose, 171 for disaccharides, and 162 for all other polysaccharides within the scope of this invention.

[0068] [-OH / starting sugar] is 2 for agarose, 4 for disaccharides, and 3 for all other polysaccharides.

[0069] Table 2 presents the formulations of silylated polysaccharide samples. The amount of polysaccharide is provided in grams (g). The amounts of catalyst and silazane are each expressed as the number of moles of sugar units per mole of a specified gram of polysaccharide (“equivalent”). Solvent concentration is expressed as the molar concentration of a specified amount of polysaccharide in the combined volume of solvent and silazane (“M”). “DP” refers to the degree of polymerization of the polysaccharide, which is the number of sugar units bonded together in the polysaccharide.

[0070]

[0071] Preparation of cross-linked polysiloxane elastomers

[0072] Table 3 lists the materials used to prepare the cross-linked polysiloxane elastomers for the samples described below, in addition to the alkenyl functional polysaccharides in Table 2.

[0073] Table 3

[0074]

[0075]

[0076] SYL-OFF and XIAMETER are trademarks of Dow Corning Corporation. CETIOL is a trademark of Corning Intellectual Property Management, Inc. CERAPHYL is a trademark of ISP Investments LLC. NEOSSANCE is a trademark of Amyris, Inc.

[0077] Crosslinked polysiloxane elastomers were prepared by hydrogenation silanization using the formulations described in Table 4, wherein the amounts of the components are in grams (g). The following reaction procedure was used. The specified amounts of vinyl-functionalized polysaccharide and solvent were added to a 20 mL scintillation vial equipped with a magnetic stir bar. Stirring was initiated and the contents were heated to 70°C for 15 minutes to dissolve the components into a homogeneous solution. The specified amounts of SiH-functionalized polysiloxane and any additional crosslinking agent were added. The reaction mixture was heated at 70°C for 10 minutes, followed by the addition of a platinum-based catalyst. Heating was continued at 70°C for an additional 3 hours. The mixture was then cooled to 25°C. A successful reaction (i.e., successful curing) was demonstrated by the formation of a gel that did not flow more than 1 cm in the scintillation vial when inverted for one minute.

[0078] Table 4 identifies the components used and their concentrations (in parentheses), in grams, except for the catalyst, which is expressed as parts by weight of Pt metal per million parts by weight of the entire mixture. Table 4 also provides the molar ratio of SiH functional groups to vinyl functional groups in the formulation, wt% of the reactants, and whether the composition was successfully cured into an elastomer.

[0079]

[0080]

[0081]

[0082] Coloring in hydrosilylation

[0083] Coloration during hydrosilylation was tested by adding silylated polysaccharide, SiH-functionalized polysiloxane 2, and xylene to a 40 mL vial in the amounts described below. A PTFE stir bar was added, and the mixture was heated to 70 °C while mixing. 150 μL of platinum catalyst was added. The reaction was continued to be heated for 2.5 hours.

[0084] Four different reaction products were evaluated using ASTM D1209-05 to determine the APHA color value for each product. The four different reaction products and their APHA color measurements are as follows:

[0085] (1) Reference = Using xylene (0.92 mL) and SiH polymer (0.35 g). SiH-functionalized polysiloxane 2 was run only under reaction conditions without reactants containing terminal olefins. The resulting APHA color was >500.

[0086] (2) Vinyl-free β-cyclodextrin = using xylene (0.92 mL), SiH-functionalized polysiloxane 2 (0.25 g), and alkenyl-functionalized polysaccharide 20 (0.20 g) as silylated polysaccharides, which are 80 mol% silylated but have fully saturated silyl groups. The resulting APHA color value is >500.

[0087] (3) 33 Mol% Vinyl β-Cyclodextrin = Using xylene (0.92 mL), SiH-functionalized polysiloxane 2 (0.25 g), and alkenyl-functionalized polysaccharide 6 (0.20 g) as silylated polysaccharides, which are 70 mol% silylated and have 33 mol% vinyl groups. The resulting APHA color value = 140.

[0088] (4) 100 mol% vinyl β-cyclodextrin = using xylene (0.92 mL), SiH-functionalized polysiloxane 2 (0.36 g), and alkenyl-functionalized polysaccharide 21 (0.09 g) as silylated polysaccharides, which are 75 mol% silylated and have 100 mol% vinyl groups. The resulting APHA color value = 50.

[0089] The results revealed that vinyl-functionalized silylated β-cyclodextrins, when included in a hydrosilylation reaction using a platinum catalyst, surprisingly achieved APHA chromaticities of less than 500, and even less than 300.

[0090] Elastomer gel paste

[0091] A gel of the crosslinked polysiloxane elastomer of the present invention and a paste of a gel of a conventional polysiloxane elastomer were prepared by subjecting the gel to shearing in a mixer while adding another solvent as described below. The sensory properties, wash durability, and solvent compatibility of the resulting paste were then characterized.

[0092] Preparation of paste samples and references

[0093] Paste Sample 1 (PS1)60.0 g of sample 54 was sheared in a Waring 7012 mixer and gradually diluted with 17.8 g of solvent 1. Mixing continued under shear for approximately 5–10 minutes until a paste with a viscosity of 300,000 mPa was obtained (using a Brookfield DV-II Plus Pro programmable viscometer with a helipath rotor (S94) at 2.5 rpm at 25°C).

[0094] Paste Sample 2 (PS2) 60.0 g of sample 55 was sheared in a Waring 7012 mixer and gradually diluted with 17.8 g of solvent 2. Mixing continued under shear for approximately 5–10 minutes until a paste with a viscosity of 400,000 mPa (2.5 RPM at 25°C using a Brookfield DV-II Plus Pro programmable viscometer with a helipath rotor (S94)) was obtained.

[0095] Paste Sample 3 (PS3) 56.0 g of sample 56 was sheared in a Waring 7012 mixer and gradually diluted with 31.1 g of solvent 1. Mixing continued under shear for approximately 5–10 minutes until a paste with a viscosity of 280,000 mPa was obtained (2.5 RPM at 25°C using a Brookfield DV-II Plus Pro programmable viscometer with a helipath rotor (S94)).

[0096] Paste Sample 4 (PS4) 1.78 g of sample 19 was sheared in a Waring 7012 mixer and gradually diluted with 6.0 g of solvent 1. Mixing continued under shear for approximately 5–10 minutes until a paste with a viscosity of 65,000 mPa was obtained (2.5 RPM at 25°C using a Brookfield DV-II Plus Pro programmable viscometer with a helipath rotor (S94)).

[0097] Paste sample 5 (PS5) 57.2 g of sample 57 was sheared in a Waring 7012 mixer and gradually diluted with 13.2 g of solvent 1. Mixing continued under shear for approximately 5–10 minutes until a paste with a viscosity of 300,000 mPa was obtained (2.5 RPM at 25°C using a Brookfield DV-II Plus Pro programmable viscometer with a helipath rotor (S94)).

[0098] Paste Reference 1 (PR1) .PR1 is available from Dow Chemical Company under the name DOWSIL TM Commercially available materials obtained from 9041 silicone elastomer blends.

[0099] Paste Reference 2 (PR2) .PR2 is available from Dow Chemical Company under the name DOWSIL TM Commercially available materials obtained from 3901 liquid satin blends.

[0100] Paste Reference 3 (PR3) .PR3 is available from Dow Chemical Company under the name DOWSIL TM Commercially available materials obtained from EL-8040 ID silicone-organic blends.

[0101] Paste Reference 4 (PR4) .PR4 is available from Dow Chemical Company under the name DOWSIL TM Commercially available materials obtained from EL-8050 ID silicone organic elastomer blends.

[0102] Paste Reference 5 (PR5) .PR5 is available from Dow Chemical Company under the name DOWSIL TM EL-7040 hydrophilic elastomer blend (DOWSIL) TM The material is commercially available and can be obtained from EL-7040 Hydro Elastomer Blend.

[0103] Paste Reference 6 (PR6) .PR6 is available from Dow Chemical Company under the name DOWSIL TM EL-9241 DM silicone elastomer blends are commercially available materials.

[0104] Characterization of paste samples and references

[0105] The paste was characterized using the following evaluation methods:

[0106] Sensory evaluation Five panel members, trained in sensory evaluation and regularly participating in sensory evaluation, washed their forearms, hands, and fingers with water containing 4.3 wt% active sodium lauryl ether sulfate, rinsed with distilled water, and dried with paper towels. A 50 mg paste sample or a previous reference was applied to the inner forearm of these panel members using a circular motion at 2 rubs per second for a maximum of 120 rubs. Panel members assessed the following skin sensory parameters on a scale of 1 to 5:

[0107] (a) Smoothness: Evaluate the uniformity of the film and the uniformity of the texture (1 = sand, and 5 = talc).

[0108] (b) Powder form: Seeking a dry, soft, smooth, and slippery feel (1 = petrolatum, and 5 = talc).

[0109] (c) Greasiness: Detection of viscous, dense coatings related to resistance (1 = talc, 5 = petrolatum)

[0110] (d) Adhesion: The stickiness or degree to which a finger adheres to the skin (1 = untreated skin, and 5 = lanolin).

[0111] (e) Humidity: The amount of liquid felt after 10 rubs (1 = talcum powder, and 5 = mineral oil).

[0112] One-way ANOVA was used to compare the assessments of each sensory attribute for all samples. If the p-value was <0.05, a post-hoc Tukey-Kramer HSD test was performed. Statistically different samples were indicated as different at the p<0.05 level.

[0113] Table 5

[0114] PS1 4.2 3.2 3.2 1.8 1.8* PS2 3.4 2.4 3.2 2.4 2.4* PS3 4.4 3.8* 1.6 1.4 2.1* PR1 3.8 2.8 2.8 2.6 2.0* PR2 4.2 1.6 1.6 2.6 4.7

[0115] * indicates a statistically significant difference from PR2 when the p-value is <0.05 according to the Tukey-Kramer HSD test.

[0116] The results in Table 5 show that the paste of the crosslinked polysiloxane elastomer of the present invention has sensory properties associated with typical silicone elastomer blends (PR1), but different from other crosslinked silicone materials. PS3 is a sample in an exemplary powder form.

[0117] Durability test Mix 8 grams of paste with 2 grams of Skolor Glare TM Purple SG-7661E pigment (from CQV Co., Ltd.) was placed in a dental cup and mixed for 20 seconds at 2300 RPM using a FlackTek DAC150 speed mixer. 0.3 g of the resulting mixture was coated onto a 4.75 cm × 5 cm collagen-coated microscope slide. The coated slide was allowed to dry at 25°C for 24 hours. The mixture was then tested by applying 0.07 g of dilution with a wet fingertip. TM A solution of detergent (a trademark of Henkel) in 0.07 g of water was applied to a coated glass slide for 20 seconds to wash the slide. Images of the slide were captured before and after washing, and analyzed using ImageJ software to determine the area of ​​remaining material. The percentage of coated area remaining after washing is shown in Table 6 as a durability value—higher values ​​are associated with higher durability.

[0118] Table 6

[0119] PR1 0 PR3 25 PR4 2 PS1 100 PS5 91 PS4 63 PS2 25

[0120] Table 6 shows that PR1 has poor wash durability. PR1 is a pure silicone paste—a paste made from silicone elastomers gelled with polysiloxane solvates. PR1 is a benchmark paste in sensory properties, but has poor wash durability.

[0121] The data in Table 6 further demonstrate that the paste of the gelled crosslinked polysiloxane elastomer of the present invention exhibits higher wash durability than the paste of a pure silicone elastomer gelled with the same solvent. A comparison of PR3 and PR4 (two siloxane elastomers gelled with isododecane) with PS1 and PS5 (the elastomers of the present invention gelled with isododecane) shows the significant improvement in wash durability of the elastomers of the present invention.

[0122] PS4 is a paste for the elastomer of the present invention, prepared as a gel in farnesane, which is diluted in isododecane during preparation. Farnesane (boiling point 252°C at 101 MPa) is a less volatile solvent than isododecane (boiling point 210°C at 101 MPa). Even with the addition of a less volatile solvent, PS4 paste exhibits higher wash durability than PR3 and PR4.

[0123] PS2 provides a paste of the elastomer of the present invention, which is prepared as a gel in farnesane and diluted in farnesane when the paste is made. Even when only a lower volatile solvent (farnesane) is used in the preparation of the gel and the paste, the paste has wash durability comparable to that of the most durable reference sample with a higher volatile solvent (isododecane).

[0124] These results demonstrate that pastes made with the polysaccharide-containing elastomers of the present invention inherently exhibit higher wash durability compared to conventional pure silicone elastomers.

[0125] Solvent compatibility Add 7.5g of paste and 2.5g of test solvent to the dental cup and mix at 2300RPM for 30 seconds using a FackTek DAC150 speed mixer. Allow the sample to stand undisturbed at 25°C for 24 hours, then assess solvent compatibility using the following scale:

[0126] 1- Clarity: The sample is not cloudy, and the mixture can be easily read when the text is placed behind it.

[0127] 2- Slight Turbidity: The sample is almost clear with only very slight turbidity detectable, and it can still be easily read through the sample when the test is placed behind it.

[0128] 3-Turbidity: The sample is not clear, and the text placed behind the sample is perceptible but cannot be read.

[0129] 4-Opaque: White solid, light cannot pass through it and it is impossible to detect anything placed behind the sample.

[0130] 5-Incompatible: Sample phase separation.

[0131] Table 7

[0132]

[0133] The data in Table 7 show that the gel paste from the cross-linked polysiloxane elastomer of the present invention has higher solvent compatibility in a wider range of solvents than the paste of the reference polysiloxane.

[0134] Hydrolytic instability of CO-Si bonds to COC bonds

[0135] The sample (15 mg) was placed in 0.6 mL of d6-acetone (sample 23) or d6-DMSO (polysaccharide 7) in a glass NMR tube. Then, 5 μL of a 9:1 v / v solution of water / trifluoroacetic acid was added, and 1H NMR spectra were acquired at the time points shown in Table 8. Mol% CO-Si hydrolysis was measured by integrating the TMS-cyclodextrin peak from δ 0.1–0.3 ppm and the hydrolyzed TMS groups from δ 0.03–0.07 ppm. Mol% COC hydrolysis was determined by evaluating CO-CH3, which was determined by evaluating the growth of any resonances present in MeOH at δ 3.31 in d6-acetone and at δ 3.16 in d6-DMSO. A white precipitate was observed in the NMR tube after the 5-hour time point for sample 23. The precipitate was separated by evaporation of the volatiles. The precipitate was soluble in d6-DMSO and was analytically consistent with the starting material, polysaccharide 7.

[0136] Table 8

[0137] 23 0 3 0 23 0.5 13 0 23 5 84 0 Polysaccharide 7 0 N / A 0 Polysaccharide 7 3 N / A 0

[0138] Sample 23 showed an increase in the amount of hydrolyzed CO-Si bonds over time, from 3% at time 0 (due to residual byproducts from the synthesis reaction) to 84% after 5 hours at room temperature. However, the methyl groups forming the COC bonds from this sample remained intact and showed no signs of hydrolysis. As a control, the original sample of methyl-β-cyclodextrin was also treated with trifluoroacetic acid as described above. This sample also showed no degradation of the COC groups after 3 hours at room temperature, demonstrating the stability of this bond.

[0139] Data confirms that the CO-Si bond has lower hydrolytic stability compared to the COC bond.

[0140] hydrophilicity of the sample

[0141] The hydrophilicity of the paste samples was assessed using contact angle measurements. The paste samples were applied as a uniform film onto a 3” × 2” glass microscope slide using a 50-micron applicator. Then, an 8 μL droplet of ultrapure (>18 M-ohm cm) water was placed on top of the film using a micropipette. The contact angle of the droplet on the film was measured using an AST Products VCA Optima video contact angle system. The contact angle was calculated using VCA-2500XE software. Contact angles below 90 degrees (°) indicate a hydrophilic film.

[0142] Table 9

[0143] PS1 103 hydrophobic PS3 94 hydrophobic PR5 58 hydrophilic PR6 103 hydrophobic

Claims

1. A composition comprising a crosslinked polysiloxane elastomer having two or more carbon-oxygen-silicon links between a polysaccharide component and a polysiloxane component, wherein the polysaccharide component is not a cellulose or starch component, and wherein the composition is a gel comprising the crosslinked polysiloxane elastomer swollen in a solvent.

2. The composition according to claim 1, wherein the polysaccharide component comprises fructose, galactose, dehydrated galactose, or glucose-linked sugar units, provided that the glucose glycosidic linkage is α-linked.

3. The composition according to any of the preceding claims, wherein the polysaccharide component has only side groups selected from the group consisting of -OSiR3 groups, -CH2OSiR3 groups, -OH and -CH2OH, in addition to the connection with the polysiloxane.

4. The composition according to any of the preceding claims, wherein the polysaccharide component is selected from the group consisting of: β-cyclodextrin, maltodextrin, pullulan, dextran, trehalose, inulin, and agarose.

5. The composition according to any of the preceding claims, wherein each polysaccharide component comprises an average of 2 to 2000 linked sugar units.

6. The composition according to claim 5, wherein the solvent is one or more solvents selected from isododecane, farnesane, undecane, n-dodecane, and tridecane.

7. The composition according to claim 1, wherein the composition is in the form of a paste obtained by subjecting the gel to shear mixing.

8. A method for preparing the composition according to claim 1, the method comprising forming the crosslinked polysiloxane elastomer by a hydrosilylation addition reaction between reactants, the reactants comprising: a. SiH-functionalized polyorganosiloxanes with an average of at least two SiH functional groups per molecule; b. An alkenyl-functionalized polysaccharide, characterized in that: i. Includes linked fructose, galactose, dehydrated galactose, or glucose units, provided that the glycosidic linkage of glucose is α-linked; ii. On average, 1 to 100 mol% of the hydroxyl groups on the alkenyl functional polysaccharide have been silylated with a -SiR3 silyl group linked to the polysaccharide via a CO-Si bond, wherein each R is independently selected from a hydrocarbon group having 1 to 12 carbon atoms, provided that on average, at least 2.0 R groups per polysaccharide are terminal alkenyl groups; and iii. The alkenyl functional polysaccharide is not silylated cellulose or silylated starch; and c. Optionally, additional crosslinking additives; The reaction is carried out in the presence of the following conditions: d. Platinum-based hydrogenation silylation catalysts; and e. Solvent.

9. The method according to claim 8, wherein the alkenyl functional polysaccharide is selected from the group consisting of: silylated β-cyclodextrin, silylated maltodextrin, silylated pullulan, silylated dextran, silylated trehalose, silylated inulin, and silylated agarose.

10. The method according to claim 8 or claim 9, wherein the solvent concentration in the gelled crosslinked polysiloxane elastomer composition is 30 wt% or more and 85 wt% or less, based on the total weight of the solvent and the crosslinked polysiloxane elastomer.

Citation Information

Patent Citations

  • Analysis method for silicon hydrogen content in hydrogen-containing silicone oil

    CN103674889A

  • Polyorganosiloxane gels having glycoside groups

    CN105829405A

  • Hydrophilic cyclodextrin-containing silicone gels

    CN112512494A

  • Silated polysaccharide process

    US5071978A